Sexually dimorphic role for vasopressin in the development of social play - Paul, Matthew J.; Terranova, Joseph I.; Probst, Clemens K.; Murray, Elaine K.; Ismail, Nafissa I.; De Vries, Geert J. (Frontiers in Behavioral Neuroscience, 2014)
Despite the well-established role of vasopressin (AVP) in adult social behavior, its role in social development is relatively unexplored. In this paper, we focus on the most prominent social behavior of juvenile rats, social play. Previous pharmacological experiments in our laboratory suggested that AVP regulates play in a sex- and brain region-specific manner in juvenile rats. Here we investigate the role of specific AVP systems in the emergence of social play. We first characterize the development of play in male and female Wistar rats and then ask whether the development of AVP mRNA expression correlates with the emergence of play. Unexpectedly, play emerged more rapidly in weanling-aged females than in males, resulting in a sex difference opposite of that typically reported for older, juvenile rats. AVP mRNA and play were correlated in males only, with a negative correlation in the bed nucleus of the stria terminalis and a positive correlation in the paraventricular nucleus of the hypothalamus. These findings support the hypothesis that AVP acts differentially on multiple systems in a sex-specific manner to regulate social play and suggest a role for PVN and BNST AVP systems in the development of play. Differential neuropeptide regulation of male and female social development may underlie well-documented sex differences in incidence, progression, and symptom severity of behavioral disorders during development.